The Role Of Business Analytics Adoption In Fostering Value Creation To Achieve Competitive Advantage In Industry 4.0 - Dian Alanudin (Eduvest - Journal of Universal Studies, 2024)
In the era of Industry 4.0, where disruption and uncertainty reign, the strategic adoption of business analytics emerges as a vital force in driving competitive advantage through value creation. This study investigates the pivotal role of business analytics adoption in fostering value creation to achieve a sustainable edge in Industry 4.0. By analyzing data from 237 E-commerce firms operating in fiercely competitive markets, the research explores the strategic imperatives for maximizing the utilization of data and information assets. It highlights the importance of integrating business analytics into organizational processes and fostering collaboration and dynamic capability to optimize decision-making and spur innovation. The findings underscore the necessity for firms to develop competencies in leveraging data-driven insights for competitive advantage. Moreover, this study contributes to bridging gaps in both Resource-Based Theory and dynamic capability literature, offering insights into practical actions for navigating the complexities of Industry 4.0. Ultimately, the research provides a comprehensive framework for understanding and implementing business analytics adoption as a strategic imperative for organizational success in the digital era, with implications for enhancing competitive advantage and driving sustained growth.